The use of YouTube in Increasing Non – English Students' Self–Confidence in Speaking - Indah Muzdalifah; Lisnawita Lisnawita; Elvira Asril; Asma Alhusna (STAI Hubbulwathan Duri, 2023)
The study aimed to determine whether the usage of YouTube can influence non-English students' self–confidence in speaking English. Besides, it increased non-English students' speaking quality when uploaded to YouTube. This study used a descriptive qualitative method. The data is taken using the test. The data in the form of numbers are described in a complete and detailed explanation and description. The result of this research found three categories of non–English speaking students. They are very good, good, and not good category. The range of very good categories between 76% - 100% was found in 12 students who achieved this score. The content of the good category between 56% - 75% was found in 16 students who achieved this score. The range of the not-good category was between 40% and 55%, with only two students in this category. Using YouTube can improve non-English students' speaking skills and increase their self-confidence to be brave when speaking on social media.